Increasing biocompatibility of scaffold made of Polyethersulfone (PES) through combining with polyaniline(PANI) - Pournaqi, Faeze; Farahmand, Mahnaz; Ardeshirylajimi, Abdolreza (Archives of Advances in Biosciences, 2016)
Today’s tissue engineering is an important and interested method to treatment of  bone lesions so tissue engineering specialists and orthopedic surgeons are forced to serve as a safe alternative to current methods.The introduction ofa scaffoldthathas thebestefficiencyisamajor challengeto scientistsand researchersin this field.The aim ofthisstudy is to investigatethe polyaniline(PANI) influence onbiocompatibilityof Polyethersulfone (PES)nanofibrousscaffold.Fabricated scaffold was structurally characterized using SEM microscope andtensile assay.Toinvestigate biocompatibility of nanofibers by MTT assay andDAPI staining, human mesenchymal stem cells were seeded on the surface of PES, PES-PANI and tissue culture polystyrene (TCPS) as control .SEM imagesshowed that thescaffoldswereflat and the average diameters ofthenanofiberswere 286 ± 588.In addition the results ofMTT assay andDAPI stainingshowedthe highestproliferation rate of cellswas observed in PES-PANIscaffoldcompared to the PES and TCPS as control.It can be concludedthatPANIwas improved three-dimensionalstructure ofPES nanofibers and causes to increase biocompatibility of PES bysupportproliferationandpenetrationof MSCs in the PESnanofibers andcould also bea good candidate forintroductionandusein the bone tissueengineeringapplication